Types and severity of sexual harassment among female college students in a non-traditional degree program. - Bacanto, Jay Ann B.
This descriptive study aimed to find out the perception of female college students in a non-traditional degree towards the types and severity of sexual harassment., Fifty-four (54) female students, who were officially enrolled in the College of Criminology at the University of Iloilo for school year 2002-2003 during the second semester, participated in the research. Perception on sexual harassment was measured using a revised scale on the perception of the types and severity of sexual harassment developed by Baker, Terpstra, and Lantz (1990). The scale has six scenarios relfecting the types and severity of sexual harrassment, whereas females working in a male-dominated workplaces were sexually harrassed by male- co-workers. The mean scores and standard deviations were utilized to interpret the data. The results of the study revealed that incidents having sexual coercion were perceived higher compared to other types of sexual harassment (X=1.17; s=3.66). Types of sexual harassment with an element of physical contact were perceived to be more sexually harassing (x=5.41; s=4.61). It further revealed that sexual harassment with physical contact were perceived most sexually harassing (x=2.43; s=1.09).